Analisis Peran Kepala Sekolah di SD Muhammadiyah Makotyamsa Kabupaten Sorong - Satriyawan, Syahrizal Bayu; Purwojuono, Ribut; Saputro, Isnaini Eddy (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
This research aims to determine and analyze the role of school principals in improving teacher professionality, the obstacles faced by school principals in increasing teacher professionality, what efforts the principal makes to increase teacher professionality at Al Azhar 4 Islamic High School Kemang Pratama. The method used in this research is a type of qualitative research. This research was written by describing or describing what the researcher saw and found. The subjects in this research were school principals, curriculum representatives, teachers and students. The results of this research show that the role of the principal in increasing the professionality of teachers at Al Azhar 4 Islamic High School Kemang Pratama Bekasi is  The principal plays a role as a leader in directing and providing direction to teachers. They are responsible for designing professional development strategies, providing training, and providing support to improve teachers' skills and knowledge. The principal also plays a role in creating a school environment that supports professional growth. Obstacles occur due to limited resources, resistance to change from some teachers, heavy workload demands, time constraints, lack of support from the education center. Techniques for increasing the professional competence of School Principals include regular training, individual approaches in developing teacher professionality, collaboration between teachers for the exchange of experiences.